2021
DOI: 10.1037/met0000303
|View full text |Cite
|
Sign up to set email alerts
|

Modeling psychopathology: From data models to formal theories.

Abstract: Over the past decade, there has been a surge of empirical research investigating mental disorders as complex systems. In this article, we investigate how to best make use of this growing body of empirical research and move the field toward its fundamental aims of explaining, predicting, and controlling psychopathology. We first review the contemporary philosophy of science literature on scientific theories and argue that fully achieving the aims of explanation, prediction, and control requires that we construc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 346 publications
(647 reference statements)
0
90
0
1
Order By: Relevance
“…Although early work on network psychopathology expressed the hope that symptoms high on strength centrality may be suitable targets for intervention whose resolution would hasten recovery from illness (e.g., McNally, 2016), such hopes presupposed that these networks, although perhaps not establishing causal relations, would at least identify a skeletal structure of the causal system of interest. Subsequent research has suggested that this is unlikely to be the case for the kinds of complex systems we should expect to see in mental health research (Haslbeck, Ryan, Robinaugh, et al, in press; Ryan et al, 2019). Moreover, reservations have arisen about whether interventions are able to selectively target high-centrality symptoms in isolation from other symptoms, akin to a gene-knockout procedure (e.g., Bringmann et al, 2019; McNally, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although early work on network psychopathology expressed the hope that symptoms high on strength centrality may be suitable targets for intervention whose resolution would hasten recovery from illness (e.g., McNally, 2016), such hopes presupposed that these networks, although perhaps not establishing causal relations, would at least identify a skeletal structure of the causal system of interest. Subsequent research has suggested that this is unlikely to be the case for the kinds of complex systems we should expect to see in mental health research (Haslbeck, Ryan, Robinaugh, et al, in press; Ryan et al, 2019). Moreover, reservations have arisen about whether interventions are able to selectively target high-centrality symptoms in isolation from other symptoms, akin to a gene-knockout procedure (e.g., Bringmann et al, 2019; McNally, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We then tested how accurate our predictions were for our regression analyses. We relied on formalized predictions from our regression models generated in the exploratory phase in our training data (see also [ 74 ]). We display these formalized predictions in table 8 .…”
Section: Confirmatory Resultsmentioning
confidence: 99%
“…Por otro lado, Norcross y colaboradores (2005) también encontraron una tendencia importante en incremento de los profesionales por adoptar teorías cognitivas e integrativas desde 1960 hasta el 2003, lo que sugiere que investigar el estado del arte de la clínica práctica actual en nuestro país, ya que los números son consistentes con la presenta investigación. Con respecto a la percepción de la atención psicológica por parte de los psicólogos, se encontró que la denominación de la persona que asiste al proceso terapéutico la mayoría mostró una tendencia a denominarlo paciente por motivos de atención clínica, y si bien es cierto que en la consulta no necesariamente se atienden siempre conductas patológicas parece ser que esto podría ser dependiente del enfoque y no del problema, lo cual la literatura sugiere es un grave error, porque desde la perspectiva actual el hecho de que una conducta sea patológica depende del grado de inadaptabilidad del sujeto y no del marco teórico desde el cual se esté interpretando (Cook et al, 2018), adicionalmente, la mayoría de la literatura psicométrica y de evaluación sugiere que para evidenciar una conducta desadaptativa en criterios estadísticos debe tener al menos 1.5 medidas de dispersión por fuera de la tendencia central, esto con el fin de evitar falsos positivos o falsos negativos (Haslbeck et al, 2021). Situación que se discutirá en un futuro artículo.…”
Section: Discussionunclassified